Análise de coerência entre cinemática e atividade muscular simulada em modelo de pêndulo invertido triplo na postura ereta quase-quieta antes e após uma perturbação mecânica - Lemes, Thiago Santana (2017)
The analysis of muscle activation and the modeling of the human body as a triple inverted pendulum reveal some interesting quasi-quiet standing posture maintenance mechanisms not observable in simpler models. Studies have shown some patterns of coordination between body segments and muscles when standing under an upright position, but due to the use of simpler models they did not reveal the exact role of the knee in the upright posture. In this study, 25 young people participated in an experiment, in which kinematic data and force platforms were collected. A complex coherence and phase analysis was used between simulation of muscle activity, body segment kinematics and inverse dynamics, in order to verify if there is a difference between the signals before and after an induced disturbance, and how the trunk and knee joint behaves in a triple inverted pendulum model of the body. Complex coherence is an analysis in the frequency domain and reveals how well two signals correspond to one another. The activation of nine muscles was simulated, and the resulting torque using the inverse dynamics at the ankle, knee and hip joints was calculated, both using OpenSim software. The trunk worked in phase with leg and thigh at low frequencies, and switched to anti-phase at high frequencies. However, the trunk does not show significant coherence with any of the muscles analyzed besides moving in delay with respect to the torque in the hip, which suggests that the trunk oscillations occur passively. However, thigh and leg muscles activated in phase with trunk muscles, suggesting a relationship between the movement of these segments. However, it has to be considered that there are limitations in the simulations of muscle activation, so that future experimental studies that confirm the data presented here are necessary. The results show no significant difference between the pre-perturbation and post-perturbation oscillations, but there is a greater variability in the angular oscillations of the segments, indicating the challenge imposed to the postural control system and the work of recovering the disturbance. Patterns of muscular activation in the ankle and pelvis were compatible with previous studies, acting to maintain upright posture.